The formation of rodingite in the Nagasaki metamorphic rocks at Nomo Peninsula, Kyushu, Japan – Zircon U–Pb and Hf isotopes and trace element evidence - Fukuyama, M.; Ogasawara, M.; Dunkley, Daniel; Wang, K.; Lee, D.; Hokada, T.; Maki, K.; Hirata, T.; Kon, Y. (Blackwell Publishing Asia, 2014)
Rodingites occur in serpentine-matrix mélange of the Nagasaki metamorphic rocks in Japan. Two types of rodingites can be distinguished on the basis of their mode of occurrence and mineralogical composition. One occurs as dikes, which contain a mineral assemblage of grossular, vesuvianite, diopside, apatite, titanite, and zircon. The other occurs as a block, which consists of zoisite, clinozoisite, diopside, chlorite, apatite, titanite, and zircon. The former type of rodingites posses two types of zircons: prismatic and porous. The prismatic zircons contain primary fluid inclusions indicating their crystallization in the presence of fluids. The porous zircons have extensive fractures filled by zircon, which are indicative of a hydrothermal origin. Both zircon types were thought to have formed under the influence of fluids. U–Pb ion probe analyses of prismatic zircons from the rodingites yield a weighted mean age of 108–105 Ma, suggesting the Early Cretaceous as the time of rodingitization in the subduction zone. Hafnium isotopic compositions of prismatic zircons are close to or overlap with the mid ocean ridge basalt (MORB) Hf isotopic ratio. This indicates that the fluid composition may have been reflected by the MORB composition during rodingitization. On the other hand, the low εHf values (11.8–18.9) of porous zircons suggest that they incorporate a small amount of Hf from fluid contaminated by subducted sediments. The rodingites are significantly enriched in Sr and depleted in large ion lithophile elements (LILE) (Cs, Rb, Ba). The fluid during rodingitization is able to extracts LILEs from the protolith of rodingites and adds Sr to the protolith of rodingites. The high field strength elements (HFSE) (Zr, Th, U, Nb, Ta) concentrations in the rodingites are similar to those of MORB, thus indicate their relatively immobile nature during rodingitization.